Hemoptysis: Is it Tuberculosis? - Bhatta, DR; Gokhale, S (International Journal of Infection and Microbiology, 2013)
INTRODUCTION: Hemoptysis is usually considered as an indication of pulmonary tuberculosis, but may be associated with various other causes. Present study will draw attention towards various causes of hemoptysis other than pulmonary tuberculosis. MATERIALS AND METHODS: This prospective study was conducted between August 2008 to May 2009 in the Department of Microbiology, Sikkim Manipal Institute of Medical Sciences, Gangtok, India. Total of 61 blood stained sputum samples were collected and examined to detect various etiological agents (bacteria, fungi and parasites) by standard techniques. Brief clinical details of patients related to their illness were recorded. RESULTS: Acid fast bacilli were demonstrated in 29.5% of cases. Klebsiella pneumoniae, Pseudomonas aeruginosa, Staphylococcus aureus, Streptococcus pneumoniae, Aspergillus niger, Candida albicans and Candida tropicalis were isolated in 8.2%, 4.9%, 6.6%, 1.6%, 3.3%, 8.2% and 3.3% cases, respectively. Patients were clinically diagnosed as pneumonia in 6.5% cases and carcinoma of lung in 3.3% of cases. CONCLUSIONS: Although pulmonary tuberculosis is the major cause of hemoptysis, other causes of hemoptysis need to be excluded. Every case of hemoptysis, if not investigated properly may be misdiagnosed as pulmonary tuberculosis. DOI: http://dx.doi.org/10.3126/ijim.v1i2.7409 Int J Infect Microbiol 2012;1(1):63-67